1987
DOI: 10.1097/00000658-198708000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipolysis in Severely Burned Children

Abstract: In this study, the rates of lipid mobilization and of lipolysis have been quantified in severely burned children. In all 12 patients studied, the basal rates were determined. In seven patients, the lipolytic responsiveness to an infusion of epinephrine (0.015 micrograms/kg/min) was tested, and in the other five patients, the response to beta-adrenergic blockade (propranolol, 1 mg/kg) was tested. The rate of appearance (Ra) of free fatty acids (FFA) was quantified by means of the infusion of 1-13C-palmitate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 20 publications
5
69
0
Order By: Relevance
“…To provide glucose, a major fuel source to vital organs, release of the above-mentioned stress mediators oppose the anabolic actions of insulin (74). By enhancing adipose tissue lipolysis (75) and skeletal muscle proteolysis (76), they increase gluconeogenic substrates, including glycerol, alanine, and lactate, thus augmenting hepatic glucose production in burn patients (72,73,77). Hyperglycemia fails to suppress hepatic glucose release during this time (23), and the suppressive effect of insulin on hepatic glucose release is attenuated, significantly contributing to posttrauma hyperglycemia (78).…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide glucose, a major fuel source to vital organs, release of the above-mentioned stress mediators oppose the anabolic actions of insulin (74). By enhancing adipose tissue lipolysis (75) and skeletal muscle proteolysis (76), they increase gluconeogenic substrates, including glycerol, alanine, and lactate, thus augmenting hepatic glucose production in burn patients (72,73,77). Hyperglycemia fails to suppress hepatic glucose release during this time (23), and the suppressive effect of insulin on hepatic glucose release is attenuated, significantly contributing to posttrauma hyperglycemia (78).…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
“…Cree et al (69) showed an impaired activation of Insulin Receptor Substrate-1 at its tyrosine binding site and an inhibition of Akt in muscle biopsies of children at 7 days postburn. The work of Wolfe et al (23,75,78,80) indicates links between impaired liver and muscle mitochondrial oxidative function, altered rates of lipolysis, and impaired insulin signaling postburn, attenuating both the suppressive actions of insulin on hepatic glucose production and on the stimulation of muscle glucose uptake. Another counterregulatory hormone of interest during stress of the critically ill is glucagon.…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
“…In order to provide glucose, a major fuel source to vital organs, release of the above mentioned stress mediators oppose the anabolic actions of insulin (74). By enhancing adipose tissue lipolysis (75) and skeletal muscle proteolysis (76), they increase gluconeogenic substrates, including glycerol, alanine and lactate, thus augmenting hepatic glucose production in burned patients (72,73,77). Hyperglycemia fails to suppress hepatic glucose release during this time (23) and the suppressive effect of insulin on hepatic glucose release is attenuated, significantly contributing to post-trauma hyperglycemia (78).…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
“…Cree et al (69) showed an impaired activation of Insulin Receptor Substrate-1 at its tyrosine binding site and an inhibition of Akt in muscle biopsies of children at seven days post-burn. Work of Wolfe et al (23,75,78,80) indicates links between impaired liver and muscle mitochondrial oxidative function, altered rates of lipolysis, and impaired insulin signaling post-burn attenuating both the suppressive actions of insulin on hepatic glucose production and on the stimulation of muscle glucose uptake. Another counter-regulatory hormone of interest during stress of the critically ill is glucagon.…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
“…It has been reported that there was no relation between the type of nutritional support and the extent of fat in®ltration in the liver (Wolfe et al, 1988b). Since the extent of increase in lipolysis in stressed patients is a function of the magnitude of sympathetic nervous system response (Wolfe et al, 1987b), it is possible that there is a direct link between the degree of stress and the rate of hepatic triglyceride production, irrespective of the nature of nutritional support. It is also possible that neither FFA appearance or de novo synthesis of fatty acids is the cause of hepatic fat accumulation.…”
Section: Consequences Of Mismatching Supply and Utilization Of Energymentioning
confidence: 99%